Experimental Investigation of Oscillation Center Displacement of Oscillating Pulsating Current Motor and Springless Compressor Drive - Senulis, A.; Guseinovienė, E.; Jankūnas, V.; Urmonienė, L.; Andziulis, A.; Didžiokas, R. (Elektronika ir Elektrotechnika, 2007)
This article presents the oscillation center displacement of oscillating pulsating current motor and springless compressor drive (OPCM-SCD) experiment and results. The goal during the experiment was to determine the efficiency coefficient η, power coefficient cosφ, input power P, DC I0 and AC IAC dependence on OPCM-SCD pulsating part center movement. The graphs provided analysis of the modification of OPCM-SCD position in the space, thyristor firing angle and creating the artificial uneven force for each different compressor cameras. Experiment results show that pulsating center has effect on the analyzed energetic characteristics: when the off-center is present these characteristics worsen. During model analysis and during the experiment dependencies I0=f(Δh) were received. We can say that their nature is similar, but because of the natural asymmetry of used model and the slight inefficiency of measurements, these dependencies only can be analyzed practically. This article also includes the possible structural scheme of control using the regular general current for thyristor stabilization of the pulsating center. Ill. 11, bibl. 8 (in English; summaries in English, Russian and Lithuanian).